Hierarchical cache-aided transmission cooperation in 5G user-centric network: Performance analysis and design insights. (1st June 2018) - Zhang, Hongtao; Chen, Ying; Yang, Zihua
Abstract: In user-centric network (UCN), potential serving small base stations (SBSs) of user equipment (UE) form a dynamic SBS group (SBSG). Cache space and transmission resource of potential serving SBSs can be considered as an entity, but joint cache-level and transmission-level cooperation of UCN has not been analyzed in literature. This paper proposes dynamic hierarchical cache-aided transmission cooperation (CATC) in UCN, and derives semi-closed expressions of caching coverage, per-user throughput, and delay using stochastic geometry. Specifically, hierarchical CATC is dynamic since SBSG changes constantly, where UE utilizes increased aggregate cache space of potential serving SBSs by searching the contents in SBSG, and interference is coordinated among SBSs within SBSG. If not accessible in SBSG, the contents are searched in serving macro base station (MBS) and other SBSs managed by serving MBS to overcome limited cache size at SBSG. Moreover, SBSs cooperatively increase content diversity in the new content eviction policy (processed-least recently used (P-LRU)). The analysis reveals the tradeoff between coverage and throughput, for although hierarchical CATC increases hit ratio and caching coverage, per-user MBS throughput is constrained due to increased load. The analytical results are verified through simulations, and show that total and SBS caching coverage are improved by 53% and 81% respectively (when cache size of SBSs equals 10), compared to state-of-art user-centric transmission scheme.